Exercise as a tool for hypertension and resistant hypertension management: current insights - Lopes, Susana (2018)
Although there has been an observed progress in the treatment of hypertension, its prevalence remains elevated and constitutes a leading cause of cardiovascular disease development. Resistant hypertension is a challenge for clinicians, as the available treatment options have reduced success. Physical activity and exercise training play an important role in the management of blood pressure. The importance of physical activity and exercise training as part of a comprehensive lifestyle intervention is acknowledged by several professional organizations in their recommendations/guidelines for the management of arterial hypertension. Aerobic exercise, dynamic resistance exercise, and concurrent training - the combination of dynamic resistance and aerobic exercise training in the same exercise session or on separate days - has been demonstrated to reduce blood pressure and help in the management of hypertension. The present review draws attention to the importance of exercise training in the management of blood pressure in both hypertension and resistant hypertension individuals.